Reputacja jako kluczowa kompetencja przedsiębiorstwa - Roszyk-Kowalska, Gabriela (The reputation as key competence of enterprise, 2006)
Key competences or there is attributes differing ability or for given enterprise package of all its own attribute and they enable obtainment of competitive superiority it. These abilities create superior value for clients than values, which offers competition of enterprise memorial. The reputation is one of such differing ability, or most important instrument of devolution of information clients.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 145-148